2013
DOI: 10.18408/ahuri-8201301
|View full text |Cite
|
Sign up to set email alerts
|

How integrated are homelessness, mental health and drug and alcohol services in Australia?

Abstract: TitleHow integrated are homelessness, mental health and drug and alcohol services in Australia? ISBN 978-1-922075-28-4Format PDF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
(62 reference statements)
1
29
0
Order By: Relevance
“…Importantly, most shelters and housing programs for the homeless in Australia require abstinence from alcohol . Considering that these facilities are often an important resource for homeless people, such as to link them in with social and health services, it means that homeless Australians with PAC are further isolated from the help that they may require in order to manage their PAC, as well as their homeless state.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, most shelters and housing programs for the homeless in Australia require abstinence from alcohol . Considering that these facilities are often an important resource for homeless people, such as to link them in with social and health services, it means that homeless Australians with PAC are further isolated from the help that they may require in order to manage their PAC, as well as their homeless state.…”
Section: Resultsmentioning
confidence: 99%
“…These providers aim for pragmatic approaches of ‘least‐worst’ homelessness, such as insecure boarding house accommodation that is seen as preferable to other options, including sleeping rough (Flatau et al . : 86). Similarly, the shortage of housing is an obstacle to the operation of street to home programmes in other states that aim to house and support homeless people with complex needs, including mental illness, and who are sleeping rough (Parsell et al .…”
Section: Policy and Service Contextmentioning
confidence: 97%
“…Housing is of central importance to people with chronic mental illness (Nelson et al 2007b;Browne and Courtney 2007), but this group frequently experiences unstable housing and homelessness (Mental Health Council of Australia 2005;Robinson 2003;Flatau et al 2013). For example, in Australia the second Australian national survey of psychosis showed that almost one-quarter (22.7 per cent) of people with psychosis were on public housing waiting lists; 5.2 per cent of participants were homeless; 12.8 per cent experienced at least one period of homelessness in the past year; and 25.2 per cent had been fearful of homelessness in the past year (Harvey et al 2012: 844).…”
Section: Policy and Service Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural factors contributing to homelessness include weak labour markets, tight housing markets and geographic factors Wood et al 2015). Individual risk factors include a history of contact with institutions, serious mental illness, drug or alcohol dependency, poor decision making, family and domestic violence, unemployment and relationship breakdown (Flatau et al 2013;Steen et al 2012;Stone et al 2015;Wood et al 2015).…”
Section: Entries Into Homelessnessmentioning
confidence: 99%